2017
DOI: 10.2147/ndt.s128811
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal whole-brain functional connectivity in patients with primary insomnia

Abstract: The investigation of the mechanism of insomnia could provide the basis for improved understanding and treatment of insomnia. The aim of this study is to investigate the abnormal functional connectivity throughout the entire brain of insomnia patients, and analyze the global distribution of these abnormalities. Whole brains of 50 patients with insomnia and 40 healthy controls were divided into 116 regions and abnormal connectivities were identified by comparing the Pearson’s correlation coefficients of each pai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 39 publications
3
41
0
2
Order By: Relevance
“…-11 -Our finding of increased hippocampal connectivity in association with insomnia is in line with two previous reports. Li et al (2017) reported increased connectivity between the hippocampus and the left orbital part of the superior frontal gyrus in insomnia. Regen et al (2016) found worse objective sleep efficiency with increasing connectivity between the hippocampus and the ventromedial prefrontal cortex.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…-11 -Our finding of increased hippocampal connectivity in association with insomnia is in line with two previous reports. Li et al (2017) reported increased connectivity between the hippocampus and the left orbital part of the superior frontal gyrus in insomnia. Regen et al (2016) found worse objective sleep efficiency with increasing connectivity between the hippocampus and the ventromedial prefrontal cortex.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Abnormal hippocampal functional connectivity in insomnia has been reported in two studies. Whole brain connectivity analysis showed increased functional connectivity between the left hippocampus and the left orbital part of the superior frontal gyrus in insomnia patients (Li et al, 2017). However, the participants were instructed to keep their eyes closed during the scan, which increases the risk of falling asleep (Tagliazucchi and Laufs, 2014), which in turn can influence the results.…”
Section: Introductionmentioning
confidence: 99%
“…FPC, distributed in the frontoparietal areas, is typically engaged in externally directed tasks and has been implicated in the management of exogenous cognitive functions (Cole & Schneider, ; Liang, Zou, He, & Yang, ; Vincent, Kahn, Snyder, Raichle, & Buckner, ). A previous study has revealed that regions related to wakefulness, emotion, attention, worry, and sensory motor showed increased functional connectivity with each other when studying the whole‐brain functional connectivity in patients with primary insomnia (Li et al., ). The increased DAN‐FPC‐positive connectivity may provide evidence for the hyperarousal model of insomnia (Bonnet & Arand, ) at the connectivity level.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple hypotheses to explain ID have been proposed, such as cognitive, physiological, and cortical arousal and dysfunction in neuronal circuitry (Espie, ; Fortier‐Brochu, Beaulieu‐Bonneau, Ivers, & Morin, ), among which the most compelling is hyperarousal model. According to the hyperarousal hypothesis, insomniacs commonly show increased glucose metabolism in multiple brain areas (Nofzinger et al., ), elevated energy requirements in gray matter areas (Harper et al., ), or altered functional connectivity between brain regions (Li et al., ). Nofzinger et al.…”
Section: Introductionmentioning
confidence: 99%
“…Thirty-eight patients with PI (16 men; mean ± standard deviation age, 40.61 years ± 9.43) were recruited from the Guangdong Second Provincial General Hospital. [20][21][22]. All previous studies were investigations of between-group differences using resting-state functional MR imaging, whereas the present study explored whether resting-state functional MR imaging could be used as a neuroimaging biomarker to identify primary insomnia.…”
Section: Participantsmentioning
confidence: 99%